The effect of brand trust on purchase intention mediated by brand preferences among generation Z consumers of healthy food products at Fit Fuel Restaurant - Braiant Iskandar Tjahyadi; Rita Komaladewi (Universitas Nusa Cendana, 2026)
This study aims to examine the effect of brand trust on purchase intention, with brand preference serving as a mediating variable among Generation Z consumers of healthy food products at Fit Fuel Salad & Smoothies Bar in Bandung. A quantitative research design was employed using survey data collected from 165 Generation Z respondents who were familiar with and interested in healthy food products. The proposed relationships were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The findings indicate that brand trust has a positive and significant effect on both brand preference and purchase intention. In addition, brand preference positively and significantly influences purchase intention and serves as a significant mediator in the relationship between brand trust and purchase intention. These findings highlight the pivotal role of brand preference as a psychological mechanism through which consumer trust translates into stronger purchase intentions. This study contributes to the branding and consumer behavior literature by providing empirical evidence on the mediating role of brand preference in the healthy food sector. The findings also offer practical implications for marketers by emphasizing the importance of building consumer trust through consistent product quality, transparent communication, and positive customer experiences to strengthen brand preference and stimulate purchase intention among Generation Z consumers. Keywords: Brand Trust; Brand Preferences; Purchase Intention; Healthy Food; Generation Z